Galectin network in osteoarthritis: galectin-4 programs a pathogenic signature of gene and effector expression in human chondrocytes in vitro - Katharina M. Pichler; Anita Fischer; Jürgen Alphonsus; Catharina Chiari; Sebastian Schmidt; Michael Kenn; Wolfgang Schreiner; Daniela Weinmann; Mario Rothbauer; Reinhard Windhager; Hans‑Joachim Gabius; Stefan Toegel (Histochemistry and Cell Biology, 2022)
Galectin-4 (Gal-4) is a member of the galectin family, which have been identified as galactose-binding proteins. Gal-4 possesses two tandem repeat carbohydrate recognition domains and acts as a cross-linking bridge in sulfatide-dependent glycoprotein routing. We herein document its upregulation in osteoarthritis (OA) in correlation with the extent of cartilage degradation in vivo. Primary human OA chondrocytes in vitro respond to carbohydrate-inhibitable Gal-4 binding with the upregulation of pro-degradative/-inflammatory proteins such as interleukin-1β (IL-1β) and matrix metalloproteinase-13 (MMP-13), as documented by RT-qPCR-based mRNA profiling and transcriptome data processing. Activation of p65 by phosphorylation of Ser536 within the NF-κB pathway and the effect of three p65 inhibitors on Gal-4 activity support downstream involvement of such signaling. In 3D (pellet) cultures, Gal-4 presence causes morphological and biochemical signs of degradation. Taken together, our findings strongly support the concept of galectins acting as a network in OA pathogenesis and suggest that blocking their activity in disease progression may become clinically relevant in the future.